Peningkatan Kemampuan Guru dalam Melaksanakan Tugas Pembelajaran Melalui Supervisi di SDN 19 Sebauk - Zawil Irham (STAIN Bengkalis, 2017)
Action Research School (PTS) aims to describe whether the guidance and supervision of the school principal may increase the ability of teachers in implementing the learning task at SDN 19 Sebauk District of Bengkalis in the academic year 2016/2017.After the action, observation/observation of teachers by principals as observer to the classical mentoring activities (the first meeting) went well. In caring about the items in the observation instruments when the teacher was implementing the learning process is still not yet mastered. The results of teacher observation by researchers during classical mentoring, judging from the activity of the 9 (nine) of PNS teachers earned an average (42,17%) categories are not good indicators of success planned (both categories: 56% -75%). This is because the teachers in implementing such assistance is still not optimal, and it still has not mastered the material on the activities of the academic supervision. Obtaining the results of the second cycle of academic supervision scored (an average of 76,92% / excellent category) and declared a success. This result is a positive impact on the efforts to optimize the implementation of the action class academic supervision. The results of the analysis of the first cycle and the second cycle analysis there is an increase of 34.75%. This means that there is the effect of supervision principals to improve the ability of teachers in implementing the learning task at SDN 19 Sebauk Bengkalis Bengkalis District School Year 2016/2017.Based on the description above can be concluded that the Capacity-Building Task Master Undertaking Learning Through Supervision at SDN 19 Sebauk District of Bengkalis Bengkalis in the school year 2016/ 2017 categorized Good.